Realizing the Distance in the Feet and Its Relation to the Accurate Layup Scoring of Basketball for Students - Saadi , Ali Hasan Neamah (International Journal of Psychosocial Rehabilitation, 2020)
Research Objective:• Knowing the values and realizing the distance in the basketball for • Knowing the values and realizing the accuracy of layup scoring in basketball for • Learn about the relationship between the perception of distance in the feet and the accuracy and layup goal of basketball for students.And the researcher assumes the following: There is a positive relationship between the realization of the distance with the feet accurately and the layup goal of basketball for studentsResearch methodology and field procedures: The researcher used the descriptive approach to its suitability to the nature of the research problem, and the research community included students of the Faculty of Physical Education and Sports Science - University of Karbala - the first stage. One division was chosen as a sample for research and by random method (the lottery), and they are Division (C), whose number is (30). The research sample formed (33.3%) of the research community, which is a record percentage that excluded students practicing the game, and verify its statistical data using the bag Statistical SPSS and research findings show:• There is a significant correlation between the perception of distance with the feet and the success of the layup scoring in basketball for students.• Students who have good perception of distance with the feet were more successful in their attempts to score